The influences of microbial colonisation and germ-free status on the chicken TCRβ repertoire - Dascalu, Stefan; Preston, Stephen G.; Dixon, Robert J.; Flammer, Patrik G.; Fiddaman, Steven; Boyd, Amy; Sealy, Joshua E.; Sadeyen, Jean-Remy; Kaspers, Bernd; Velge, Philippe; Iqbal, Munir; Bonsall, Michael B.; et al. (Frontiers in Immunology, 2023)
Microbial colonisation is paramount to the normal development of the immune system, particularly at mucosal sites. However, the relationships between the microbiome and the adaptive immune repertoire have mostly been explored in rodents and humans. Here, we report a high-throughput sequencing analysis of the chicken TCRβ repertoire and the influences of microbial colonisation on tissue-resident TCRβ+ cells. The results reveal that the microbiome is an important driver of TCRβ diversity in both intestinal tissues and the bursa of Fabricius, but not in the spleen. Of note, public TCRβ sequences (shared across individuals) make a substantial contribution to the repertoire. Additionally, different tissues exhibit biases in terms of their V family and J gene usage, and these effects were influenced by the gut-associated microbiome. TCRβ clonal expansions were identified in both colonised and germ-free birds, but differences between the groups were indicative of an influence of the microbiota. Together, these findings provide an insight into the avian adaptive immune system and the influence of the microbiota on the TCRβ repertoire.